Fall of development administration (Note) - Sarkar, Kanak Chandra (1996)
With a brief conceptual thrust, the author identifies the factors that have contributed to the decline of development administration as reflecting from four decades of development experience. - Reproduced
Keywords: Note; Development administration - India; Development policy; Public administration